COVID-19 Worries and Behavior Changes in Older and Younger Men and Women. (19th May 2020) - Barber, Sarah J; Kim, Hyunji
Abstract: Objectives: The case fatality rate of coronavirus disease 2019 (COVID-19) is higher among older adults than younger adults and is also higher among men than women. However, worry, which is a key motivator of behavioral health changes, occurs less frequently for older than younger adults, and less frequently for men than women. Building on this, we tested whether older adults–and particularly older men—would report the least amount of COVID-19 worry and also fewer COVID-19 behavior changes. Method: From March 23–31, 2020, we administered an online questionnaire assessing COVID-19 perceptions, worries, and behavior changes. Participants were a convenience sample of U.S. residents, who were community-dwelling younger adults (18–35) or older adults (65–81). Analyses included 146 younger adults (68 men, 78 women) and 156 older adults (82 men, 74 women). Participants were predominately white, living in suburban/urban areas, and had completed some college. Results: During the early phase of the outbreak in the United States, older adults perceived the risks of COVID-19 to be higher than did younger adults. Despite this, older men were comparatively less worried about COVID-19 than their younger counterparts. Compared with the other participants, older men had also implemented the fewest behavior changes. Discussion: Interventions are needed to increase COVID-19 behavior changes in older men. These results also highlight the importance of understanding emotional responses to COVID-19, as these are predictive of their behavioral responses.